Model Power Sistem Stabilizer Berbasis Standar IEEE untuk Stabilitas Transien Sistem Tenaga Listrik - Jamal, Agus (Semesta Teknika, 2010)
Power System Stabilizers (PSS) are added to excitation systems, in order to enhance the damping of electric power system during low frequency oscillations. For large scale power systems comprising of many interconnected machines, the PSS parameter tuning is a complex exercise due to the presence of several poorly damped modes of oscillation. The problem is further being complicated by continuous variation in power system operating conditions. In the simultaneous tuning approach, exhaustive computational tools are required to obtain optim um parameter settings for the PSS, while in the case of sequential tuning, although the computational load is fewer, evaluating the tuning sequence is an additional requirement. There is a further problem of eigenvalue drift. This research proposes the PSS model based on IEEE Standard 421.5 PSS 4B for designing robust power system stabilizers for a multi machine system. Simulations were carried out using several fault tests at transmission line on a Two-Area Multimachine Power System. As a reference the PSS model, Delta w PSS and Delta Pa PSS has been used for comparison with the PSS under consideration. The result shows that power transfer response using the model is more robust than Delta w PSS and Delta Pa PSS, especially for three phase faults and phase to ground faults.